Crítica literária e sociedade: como representa o texto literário? - Juan Pablo Chiappara (Ciências Sociais Unisinos)
This article discusses, from a theoretical point of view, the paradoxical relationship between literature and society. On the one hand, it criticizes a reading of literature with a sociologizing bias disseminated by the culturalist critique, but tries to retrieve positive aspects mentioned by authors such as Mignolo, Moreiras, Polar and Bhabba. On the other hand, it proposes a reading of literarature that asks about what it means to represent when one is in the literary realm. Thus, it poses the idea of thinking on the basis of the concept of paratopia, suggested by Maingueneau in the early 90s in the French Analysis of Discourse. In Cultural Studies, some concepts by Homi Bhabba are reconsidered, as they offer a theoretical point of view aligned with an idea of representation that does not take for granted a smooth or simplified passage from the literary text to the social or from the social to the text. Nowadays the relationship between society and literary discourse remains open. The 20th century has tried various theoretical solutions: literary structuralism believed in immanence, a post-structuralism crossed immanence and culture. Later on a certain literary critique seems to emphasize the documental aspect of literary works, giving up their aesthetical character and the differentiated conditions of social functioning that it creates. So, this article ends up being an invitation to reflect on and dialogue with thinkers from other areas of social studies who intend to deal with literary texts in their history, politics, sociology and culture works and who, with their theoretical background and practices, will be able to produce new reflections on the issue raised.